The Relation of Avian Influenza A H5N1 in Human and Strategies Control in Kamphaengphet Province 2004 - อภิวัจนีวงศ์ , สวัสดิ์ (Journal of Health Science of Thailand, 2021)
The descriptive study was a case study of avian influenza A HSN1 emergence within a cluster of a family of a probable case in Kamphaengphet province, based on the possibility of person to person transmission. The assessment of the epidemiologic investigations of the cluster of a girl, her mother and aunt was carried out and the provincial control strategies and action plan were then spelled out during 23 September - 31 December 2004. In September 2004, Kamphaengphet province reported a fatal probable avian influenza case of an 11-year-old girl. The surveillance of influenza A HSNI of the Ministry of Public Health netted in two confirmed cases of siblings - her mother and aunt -within the next fortnight. The first patient died, leaving limited amount of serum sample which failed to show antibody to avian influenza A H5N1 and remained a probable case. On the 12th days, her mother died after being in a very close contact with the first patient during her final days without any protection. In an autopsy, lung tissue of the mother was positive for influenza A H5N1 reportedly by Real Time Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) The girl lived with the aunt yet both were not in body contact with dying chickens in their compound. Only the girl's unsealed sleeping quarter was right above where the chickens perched at night. As the aunt, to a more limited extent and the mother took turn to unprotectively provide nursing care for the first patient in a hospital, they both feft ill and the nasopharyngeal swab of the aunt were also positive for the same virus. However she promptly received anti-viral drug and survived. Combatting the disease, three strategies control were adopted, firstly viral control in poultry; secondly, surveillance of the avian influenza and medical treatment in human: thirdly, risk communication